(untitled) (International Journal of Communication Systems and Network Technologies, 2020)
EDM offers numerous diversity. Wire cut EDM is one of the most emerging modern techniques for machining materials that offers more hardness while cutting and also offers resistance to generate intricate shapes by pedestrian methods. The optimum employment of the capacity of wire cut EDM requisites orthodox selection of machining parameters choosing SS316 as work piece. Using TAGUCHI’S L9 orthogonal array, no. of experiments to be conducted are finalised and Pulse-on time (Ton), Pulse-off time (Toff), Peak-current (Ip) & Wire feed rate were designated as input parameters. Three different levels of each parameter were plumped for shepherding the experiments. The responses quantified were Material Removal Rate (MRR), Kerf (width of cut) and Surface Roughness (Ra). One of the Multi Criteria Decision Making (MCDM) methods namely Grey Relation Analysis (GRA) is compassed to identify the optimum input parameter to generate higher assay of MRR and lower assay of Surface roughness and Kerf.